Consumo de frutas e vegetais por pacientes com doença pulmonar obstrutiva crônica e sua relação com o status da doença - Amaral, Vinícius Araújo (Universidade do Vale do Rio dos Sinos, 2019)
The intake of fruits and vegetables has been associated to the improvement of pulmonary function in those patients who have the Chronic Obstructive Lung Disease. Until the present moment there is not enough research that demonstrate association between diet and the staging of the disease, designed by the Global Initiative for Chronic Obstructive Lung Disease protocol. This observational and cross-sectional research assessed the relation between the intake of fruits and vegetables and the staging of the disease. Thirty-two chronic patients were evaluated, men and women between 55 and 93 years old, and submitted to a clinical evaluation for the staging of the disease designed by the protocol. The patients were divided into two groups according to the highest frequency of symptoms (A/C and B/D) and had answered a Food Frequency Questionnaire. There was no statistically significant difference between fruit consumption and disease staging in both groups (p = 0.920 and p = 0.562). The same result was found in relation to vegetable consumption (p = 0.064 and p = 0.483). The results showed a tendency for the patients with B/D staging (who present more symptoms) to consume fewer vegetables when compared to those with A/C staging (with less symptoms), (p = 0.064). The result of this study did not show a significant association between the frequency and the amount of fruit and vegetable consumption with the staging of the disease.
Keywords: DPOC; Frutas; Vegetais; ABCD; Fruits; Vegetables; GOLD; ACCNPQ::Ciências da Saúde::Nutrição